Primary Advanced Squamous Cell Carcinoma of the Temporal Bone: A Single‐Center Clinical Study. (8th April 2020) - Komune, Noritaka; Noda, Teppei; Kogo, Ryunosuke; Miyazaki, Masaru; Tsuchihashi, Nana A.; Hongo, Takahiro; Koike, Kensuke; Sato, Kuniaki; Uchi, Rhutaro; Wakasaki, Takahiro; Matsumoto, Nozomu; Yasumatsu, Ryuji; et al.
Abstract : Objectives/Hypothesis: The extreme rarity of temporal bone squamous cell carcinoma (TB‐SCC) has delayed the accumulation of high‐quality clinical evidence. For the purposes of retrospective meta‐analysis in the future, a large dataset with information from various institutions would be ideal. Our objective here was to retrospectively review cases of TB‐SCC encountered at a single tertiary referral center and explore survival outcomes and prognostic factors. Study Design: Retrospective chart review. Methods: The medical records of all TB‐SCC cases were retrospectively reviewed. The resulting dataset contained 71 cases of primary cancer eligible for initial definitive (curative) treatment. Results: T4 status was associated with lower disease‐specific 5‐year survival than T1 to T3 staging (T1: 100%, T2: 92%, T3: 86%, T4: 51%). Survival was significantly higher in operable than in inoperable cases, even when restricted to advanced (T3/T4) cancers. The tumor extension to the middle ear cavity was observed in 13/17 of T3 cases, but it was not associated with poor survival. In addition, among operable cases, negative surgical margins were associated with significantly higher survival than positive margins. Conclusions: Definitive treatments can offer disease‐specific 5‐year survival of over 85% in T1 to T3 cases of TB‐SCC. The tumor extension to the middle ear cavity is not associated with poor survival. T4 status, inoperability, nodal invasion, and positive surgical margin are identified as a predictor of poor prognosis. Still, the matter of how to deal with unresectable tumors remains an outstanding issue in the treatment of TB‐SCC. Level of Evidence: 4 Laryngoscope, 131:E583–E589, 2021